Stability and change in autobiographical reasoning: A 4‐year longitudinal study of narrative identity development. Issue 3 (30th September 2021) - McLean, Kate C.; Dunlap, David; Jennings, Sarah C.; Litvitskiy, Nicole S.; Lilgendahl, Jennifer P.
Abstract: Objective: Research on personality development has traditionally focused on rank‐order stability and mean‐level change in the context of personality traits. The present study expands this approach to the examination of change and stability at another level of personality—narrative identity—by focusing on autobiographical reasoning. Drawing from theory in personality and developmental science, we examine stability and change in exploratory processing and positive and negative self‐event connections. Method: We take advantage of a longitudinal study of emerging adult personality and identity development, which includes four waves of data across 4 years, examining reasoning in two domains of identity, academics, and romance ( n = 1520 narratives; n = 176–638 participants, depending on the analysis). Results: We found moderate rank‐order stability in autobiographical reasoning, but more so for exploratory processing than self‐event connections. We found mean‐level increases for exploratory processing in the context of romance and stability in the context of academics. For self‐event connections, we saw a decrease for positive connections, and for negative connections about romance, with stability for negative connections about academics. Conclusions: Implications include developmental differences in types of reasoning as well as the sensitivity of narrative identity to revealing the contextual nature of personality development.